2017
DOI: 10.1016/j.ymgme.2016.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Glycosaminoglycan levels in dried blood spots of patients with mucopolysaccharidoses and mucolipidoses

Abstract: Mucopolysaccharidoses (MPSs) and mucolipidoses (ML) are groups of lysosomal storage disorders in which lysosomal hydrolases are deficient leading to accumulation of undegraded glycosaminoglycans (GAGs), throughout the body, subsequently resulting in progressive damage to multiple tissues and organs. Assays using tandem mass spectrometry (MS/MS) have been established to measure GAGs in serum or plasma from MPS and ML patients, but few studies were performed to determine whether these assays are sufficiently rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 74 publications
(80 reference statements)
2
33
0
Order By: Relevance
“…The use of glycosaminoglycans (GAGs) as biomarkers for the diagnosis of neonatal MPS has been recently proposed by Kubaski as a first tier test [39]. Retrospective analysis of GAGs DBS levels in our study showed elevated levels of heparan and dermatan sulphates in the two patients carry pathogenic mutations and normal in all patients with pseudodeficiency alleles.…”
Section: Discussionsupporting
confidence: 48%
“…The use of glycosaminoglycans (GAGs) as biomarkers for the diagnosis of neonatal MPS has been recently proposed by Kubaski as a first tier test [39]. Retrospective analysis of GAGs DBS levels in our study showed elevated levels of heparan and dermatan sulphates in the two patients carry pathogenic mutations and normal in all patients with pseudodeficiency alleles.…”
Section: Discussionsupporting
confidence: 48%
“…GAGs can be quantified in: urine [34,[49][50][51][52][53][54], serum/plasma [34,48,[54][55][56], dried blood spots [57][58][59] (Figure 3), amniotic fluid [60], cerebrospinal fluid [34,61], cultured cells [34], and tissues [62]. Some of these assays can be used for newborn screening of MPSs [57,63] or even to allow the discrimination of specific disease subtypes [53]. Another biomarker that can be used is dipeptidyl peptidase (DDP) IV (CD26).…”
Section: Biomarkersmentioning
confidence: 99%
“…However, it should be noted that MPS patients with attenuated phenotypes may have false-negative results due to lower GAG levels [9]. The determination of GAGs in dried blood spot (DBS) is a rather complicated method, which is not carried out in all laboratories [10].…”
Section: Introductionmentioning
confidence: 99%